2021
DOI: 10.1002/cjoc.202100641
|View full text |Cite
|
Sign up to set email alerts
|

Tuning the Excited State of Tetradentate Pd(II) and Pt(II) Complexes through Benzannulated N‐Heteroaromatic Ring and Central Metal

Abstract: A series of tetradentate Pd(II) and Pt(II) complexes containing fused 5/6/6 metallocycles with phenyl N-heteroaromatic benzo[d]imidazole (pbiz), benzo[d]oxazole (pboz) or benzo [d]thiazole (pbthz)-containing ligands was developed. Systematic studies by experiments and theoretical calculations reveal that both the central metal and the benzannulated N-heteroaromatic ring have significant influence on the electrochemical, photophysical and excited-state properties of the Pd(II) and Pt(II) complexes. In identical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 73 publications
0
8
0
Order By: Relevance
“…Additionally, the Pd(II) complexes are strongly emissive in various matrices and achieve quantum efficiencies of up to 51%. In line with these results, tetradentate Pd(II) complexes 67 – 69 containing fused 5/6/6 metallocycles ( Figure 20 ) from benzo[d]imidazole Pd(pbiz) 67 , benzo[d]oxazole Pd(pboz) 68 , or benzo[d]thiazole Pd(pbthz) 69 were also obtained [ 85 ].…”
Section: Orthopalladated Ligandsmentioning
confidence: 55%
See 1 more Smart Citation
“…Additionally, the Pd(II) complexes are strongly emissive in various matrices and achieve quantum efficiencies of up to 51%. In line with these results, tetradentate Pd(II) complexes 67 – 69 containing fused 5/6/6 metallocycles ( Figure 20 ) from benzo[d]imidazole Pd(pbiz) 67 , benzo[d]oxazole Pd(pboz) 68 , or benzo[d]thiazole Pd(pbthz) 69 were also obtained [ 85 ].…”
Section: Orthopalladated Ligandsmentioning
confidence: 55%
“… Synthesis and chemical structures of the 5/6/6 Pd(II) complexes 57 – 69 with tetradentate ligands. Adapted from [ 84 , 85 ]. …”
Section: Figurementioning
confidence: 99%
“…All the 8-phenylquinoline-based Pt­(II) complexes exhibited well-defined reversible redox processes except the quasi-reversible reduction process of PtYL3 (Figure ), indicating the good electrochemical stabilities of the Pt­(II) complexes. In contrast, most of the previously reported tetradentate Pt­(II) and Pd­(II) complexes showed irreversible oxidation processes. ,, ,, PtYL1 , PtYL2 , and PtYL3 had similar oxidation potentials of 0.20, 0.20, and 0.21 V, respectively; however, their reduction potentials were significantly different, which were −1.97, −2.02, −1.91 eV, respectively (Table ); these results revealed that their oxidation processes were mainly on the electron-rich Pt-carbazole moieties, and the reduction processes were dominantly on the electron-deficient quinoline moieties. The introduction of the electron-donating tBu group into the 6-position of the quinoline made the reduction of PtYL2 to be harder than that of PtYL1 ; in contrast, the phenyl group extended the π-conjugation and enabled PtYL3 easier to be reduced.…”
Section: Resultsmentioning
confidence: 77%
“…Moreover, PtYL3 also exhibited two distinct molecular conformations with dihedral angles between the terminal quinoline and carbazole rings of ∠A/B = 60.61°and ∠A′/B′ = 55.07°, respectively (Figure 5a and S3); a similar result was also observed in our reported Pt(bp-10) and Pt(bp-11) with fused 6/5/6 metallocycles. 27 DFT calculations [24][25][26][27]29,30 showed that the bond lengths, bond angles, and dihedral angles of the S 0 states of PtYL1, PtYL2, and PtYL3 were in good agreement with those of the single crystal structure of PtYL3; however, the C 1 −Pt−N 3 bond angles of T 1 states of PtYL1, PtYL2, and PtYL3 (162.13, 162.29, and 162.17°) were significantly smaller than those of their S 0 states (165.63, 165.69, and 165.72°) (Tables 1 and S3); this indicated that the carbazole rings were away from the molecular core in T 1 states compared to S 0 states, which was also supported by the increased dihedral angles of their T 1 states (Table 1). The above results together with the high reaction yields of the metallization revealed that the molecular core of this 6/6/6 metallocycle system had a certain degree of flexibility, enabling the ligand to coordinate well with the central Pt(II) ion.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation